Численное решение задачи о свободных колебаниях пологих оболочек переменной толщины в уточненной постановке - Григоренко, А.Я.; Пархоменко, А.Ю. (Видавничий дім "Академперіодика" НАН України, 2009)
Розглянуто власнi коливання прямокутних в планi пологих оболонок змiнної товщини в уточненiй постановцi на основi методу сплайн-апроксимацiї невiдомих функцiй. Розрахунки частот виконанi для рiзноманiтних типiв граничних умов. Дослiджено залежнiсть власних частот коливань вiд кривизни серединної поверхнi оболонки. Natural vibrations of shallow shells with rectangular plan and variable thickness in refined statement are considered. The approach is based on the method of spline-approximation of unknown functions. Calculations of frequencies are carried out for different types of boundary conditions. The dependence of the eigenfrequencies of vibrations on the mid-surface curvature is investigated.